# Changing the Subject of a Formula

1. Oct 2, 2007

### LightbulbSun

1. The problem statement, all variables and given/known data

Express the formula for converting Celsius temperatures to Fahrenheit.

2. Relevant equations

C= (F+40)(5/9) - 40

3. The attempt at a solution

C= (F+40)(5/9) - 40
C- 40= (F+40 - 40)(5/9) - 40
(C-40)9/5= F(9/5)(5/9) - 40
(C - 40)9/5 + 40= F - 40 + 40

F= (C - 40)9/5 + 40

Answer: F= (C + 40)9/5 - 40

Could someone please explain to me why the operation signs in the (C + 40) and - 40 are opposite from the solution I came up with?

2. Oct 2, 2007

### cristo

Staff Emeritus
You made a mistake going from this line to the one below.
You need to add 40 to both sides.. I don't know where you've got that 40 from inside the brackets. The next line should read
C+40=(F+40)(5/9)

Now, what do you think you'd do next?

3. Oct 2, 2007

### LightbulbSun

OH! I know what I did wrong. I started from within the brackets first and got rid of the +40 next to the F instead of getting rid of the -40 on the outside. Now I see where I went wrong. Thank you.